The Effect of PhET Simulation in Science Learning of Static Fluid Pressure Topics towards Students’ Creative Thinking Skill - Luthfin Afafa; Indrawati Indrawati; Agustiningsih Agustiningsih (Pancaran Pendidikan, 2021)
This study aims to see is there a significant effect of the use of PhET simulations in science learning of static liquid pressure topics towards creative thinking skill of middle school students. This research was conducted at SMPIT Al-Ghozali Jember in 8th grade of C class and D class where each class consisted of 21 female students. The design of this research is Control Group Pretest-Posttest in which the learning in experimental class uses the PhET simulation while in control class uses the experimental video. The results of Wilcoxon Signed-Rank Test on students' creative thinking skill test scores are differed significantly both in the experimental class and the control class. The results of Mann-Whitney test are the students' student worksheets in the experimental class differed significantly from the control class. It can be concluded that there is a significant effect of the use of PhET simulations in this study.